Two-stage repeated-batch fermentation of immobilized Clostridium beijerinckii on oil palm fronds for solvents production. Issue 8 (August 2015) - Loyarkat, Sawang; Cheirsilp, Benjamas; Prasertsan, Poonsuk
Graphical abstract